Histological structure of Pectoralis thoracicus, small intestine, and growth performance of broiler chicken after supplementation of peanut hulls (Arachis hypogaea L.) - Lembayu, Rana Puti Lembayu; Armandu, Alfonsus Chrystian; Saragih, Hendry Trisakti (Faculty of Animal Science, Universitas Brawijaya, 2022)
The main factor that must be considered in achieving the success of the broiler industry is feed. Processed peanuts from home industries produce waste material in the form of peanut hulls. This study aims to determine the effect of peanut hulls supplementation (PHS) on feed on the histological structure of the Pectoralis thoracicus (PT) muscle, small intestine, and the growth performance of broiler chickens. This study used 360 chickens then divided into 4 treatment groups with each group amounting to 90 with 3 replications. The control group (K) was given basal feed, perlakuan 1 (P1) group with PHS 0.25% /kg basal feed, group P2 with PHS 0.5%/kg basal feed, and group P3 with PHS 1%/kg basal feed. The treatment was carried out until the chicken was 18 days old. The parameters observed were chicken body weight at post-hatch age, 3, 6, 9, 12, 15, and 18 days, feed conversion ratio (FCR), histological structure of pectoralis muscle, and small intestine. Data were analyzed using One-way ANOVA, significance (P≤0.05). The results showed that body weight and FCR values of groups P1, P2, P3 were significant towards the control. The results of the pectoralis muscle treatment group were increased significantly compared to the control. The morphological results of duodenum and jejunum groups P1, P2, P3 were significantly increased towards the control. The conclusions of this study indicate that PHS in feed shows improved body weight, the FCR value, muscle performance of PT, and structure of small intestine of broiler chickens with the addition of the most optimal supplement of peanut hulls, which is 0.5%/kg basal diet.